Diagnostic validity of p16, E-cadherin, cyclin D1, p53, and HPV E6/E7 mRNA in CIN 3-like squamous cell carcinoma of the cervix - Xing, Zhao; Danhua, Shen; Xiaobo, Zhang (Frontiers in Oncology, 2024)
Cervical squamous cell carcinoma (SCC) is the second or third most common cancer among women worldwide. Cervical SCCs exhibit variations in their patterns of growth, cell types, and degrees of differentiation. To date, numerous histologic subtypes have been recognized, whereas some rare variant patterns remain unidentified. Cervical intraepithelial neoplasia grade 3 (CIN 3)-like SCC is a recently identified deceptive growth pattern that closely mimics endocervical crypt involvement by CIN 3. As CIN 3-like SCC is indistinguishable from endocervical crypt involvement by CIN 3, it poses a significant challenge for pathologists. Herein, we examined 23 cases of CIN 3-like SCC, 6 of which also had concomitant conventional invasive SCC, and 9 cases of endocervical crypt involvement by CIN 3 as a control group.Immunohistochemistry was used to investigate the expression of p16, E-cadherin, cyclin D1, and p53, and the expression of human papillomavirus (HPV) E6/E7 mRNA, the key virus carcinogen of HPV, was detected. The clinicopathological, immunohistochemical, and molecular characteristics of endocervical crypt involvement by CIN 3, CIN 3-like SCC, and the concomitant conventional invasive SCC element were examined. CIN 3-like SCC exhibited a characteristic morphology similar to endocervical crypt involvement by CIN 3, with pushing borders invading into the wall of the cervix, often to a significant depth in most cases.Immunophenotypic features of E-cadherin, p16, cyclin D1, and p53 differed between CIN 3-like SCC and conventional invasive SCC, both in staining intensity and region. E6/E7 mRNA expression was higher in CIN 3-like SCC than in endocervical crypt involvement by CIN 3 (P < 0.05).